The anaerobic endurance of elite soccer players improved after a high-intensity training intervention in the 8-week conditioning program - Sporis, G.; Ruzic, L.; Leko, G. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to evaluate changes in anaerobic endurance in elite First-league soccer players throughout 2 consecutive seasons, in 2 phases, with and without high-intensity situational drills. Eighteen soccer players were tested before and after the 8-week summer conditioning and again in the next season. The measured variables included 300-yard shuttle run test, maximal heart rate, and maximal blood lactate at the end of the test. During the first phase of the study, the traditional sprint training was performed only 2 × weeks and consisted of 15 bouts of straight-line sprinting. In the second year the 4 × 4 min drills at an intensity of 90-95% of HRmax, separated by periods of 3-minute technical drills at 55-65% of HRmax were introduced. Statistical significance was set at P < 0.05. The traditional conditioning program conducted during the first year of the study did not elicit an improvement in anaerobic endurance as recorded in the 300-yard shuttle run test. After the intervention, the overall test running time improved significantly (55.74 ± 1.63 s vs. 56.99 ± 1.64 s; P < 0.05) with the maximal blood lactate at the end of the test significantly greater (15.4 ± 1.23 mmol/L vs. 13.5 ± 1.12 mmol/L. P < 0.01). As a result, this study showed some indication that situational high-intensity task training was more efficient than straight-line sprinting in improving anaerobic endurance measured by the 300-yard shuttle run test.